2010
DOI: 10.1063/1.3464564
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying ionic properties of a liquid-crystal cell

Abstract: This work investigates time-evolved ionic characteristics of a homogeneously aligned cell composed of a low-resistivity nematic liquid crystal. The influence of montmorillonite as a nanoadditive is studied on the dielectric spectrum of the cell. The incorporation of the inorganic nanoplatelets into the nematic leads to decrease in conductivity in the frequency range from 10 Hz to at least 10 kHz. The dielectric spectroscopic results show that the conductivity, ionic concentration, and diffusion constant of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Typically, an octahedral m at the same concentration) in liquid crystals. It was also observed that the efficiency to trap ions by nano-clay was varying in time [213]. More efficient ion trapping in liquid crystals can be achieved by combining low concentrations of nano-clay with comparable amounts of carbon nanotubes [214].…”
Section: Flcmentioning
confidence: 79%
See 2 more Smart Citations
“…Typically, an octahedral m at the same concentration) in liquid crystals. It was also observed that the efficiency to trap ions by nano-clay was varying in time [213]. More efficient ion trapping in liquid crystals can be achieved by combining low concentrations of nano-clay with comparable amounts of carbon nanotubes [214].…”
Section: Flcmentioning
confidence: 79%
“…Very interesting electrical behavior was found in liquid crystal systems doped with montmorillonite platelets [211][212][213][214][215][216][217]. Montmorillonite is a type of smectic clays characterized by a sandwich "tetrahedral-octahedral-tetrahedral" structure made of aluminosilicate lamellar materials.…”
Section: Flcmentioning
confidence: 99%
See 1 more Smart Citation
“…H.H. Liu and W. Lee have studied dielectric properties of MMT doped nematic LC E7 and have found that, in the low frequency region (f b 10 Hz), the dielectric permittivity is governed by electrode polarization and space charge polarization [29]. As frequency is inversely proportional to the time, at high frequencies, molecules have less time to cope with an applied electric field.…”
Section: Dielectric Responsementioning
confidence: 98%
“…Lee et al [13] observed that a degraded nematic LC material could be recovered by adding complex coordination polymers via chemical adsorption. Liu et al [14] showed that inorganic montmorillonite (MMT) nano-platelets were able to suppress the ionic effect by trapping the ions. Onishi et al [15] developed a FLC display device with good display quality without the deterioration of display characteristics, as a result of trapping the ionic impurities effectively by adding an organic material which traps ions and lowers conductivity of a LC layer.…”
mentioning
confidence: 99%